2011
DOI: 10.1016/j.intcom.2011.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Task and user effects on reading patterns in information search

Abstract: a b s t r a c tWe report on an investigation into people's behaviors on information search tasks, specifically the relation between eye movement patterns and task characteristics. We conducted two independent user studies (n = 32 and n = 40), one with journalism tasks and the other with genomics tasks. The tasks were constructed to represent information needs of these two different users groups and to vary in several dimensions according to a task classification scheme. For each participant we classified eye g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 73 publications
2
33
0
Order By: Relevance
“…Note that within each user there are likely also effects on search behavior that can be attributed to the search task that they are attempting. In prior studies, search task has been shown to have a significant effect on users' search behavior [7][10]. Such effects are largely removed by averaging across all search behavior for a particular user.…”
Section: Discussionmentioning
confidence: 99%
“…Note that within each user there are likely also effects on search behavior that can be attributed to the search task that they are attempting. In prior studies, search task has been shown to have a significant effect on users' search behavior [7][10]. Such effects are largely removed by averaging across all search behavior for a particular user.…”
Section: Discussionmentioning
confidence: 99%
“…We use a similar approach to [Cole et al, 2011] which is briefly summarized below. We implemented a simple, two-state, lineoriented reading model incorporating main assumptions from the E-Z Reader model [Reichle et al, 2006;Rayner et al, 2011], such as that lexical processing of words is serial, one word at a time in the order of word appearance in text, and that more than one word can be processed on a fixation, because next word can be processed in parafoveal view.…”
Section: Eye Movement Analysismentioning
confidence: 99%
“…Cole et al [8] identified differences in reading patterns associated with different task characteristics and page types. Aula et al [3] identified two general patterns that people used in examining search results: exhaustive evaluators (54% of the participants who looked at more than half of the visible results for more than half the tasks) and economic evaluators (46% of the participants).…”
Section: Related Workmentioning
confidence: 99%
“…Previous work has shown that task and query characteristics impact search behavior. Cole et al [8] found significant differences in how users read results depending on the task. Downey et al [11] showed that user behavior following a query varied significantly with popularity.…”
Section: Clusteringmentioning
confidence: 99%